Perbedaan Teknik Relaksasi Pernafasan Dalam dengan Aromaterapi Lavender terhadap Intensitas Nyeri Tusukan Jarum Anestesi Spinal - Yustika , Fatikhah Frida; Mardalena, Ida; Endarwati, Titik (Poltekkes Kemenkes Yogyakarta, 2024)
Spinal anaesthetic needle prick pain is an unpleasant experience that results in losses from spinal anaesthesia, so it needs to be treated. Deep breathing relaxation techniques and lavender aromatherapy are effective non-pharmacological pain management methods. In addition to increasing comfort, reducing pain can also provide convenience and speed in the process of injecting spinal anesthetic needles. The purpose of this study was to investigate the effects of deep breathing relaxation techniques and lavender aromatherapy on the pain intensity of spinal anaesthetic needle pricks at Kardinah Hospital, Tegal. This study employed a quasi-experiment research method, utilizing a two-group post-test design. The sampling technique used purposive sampling with a total of 72 respondents who were divided into groups of deep breathing relaxation techniques and lavender aromatherapy. Data analysis used the Mann-Whitney The results of the non-parametric statistical test with the Man Whitney test obtained p = 0.000 (p <0.05), so Ha was accepted, meaning that there was a difference in the pain intensity of spinal needle stick anesthesia given deep breathing relaxation techniques and lavender aromatherapy. rapy. The study concluded that there were differences in the pain intensity of spinal anaesthetic needle pricks at Kardinah Hospital, Tegal, between deep breathing relaxation techniques and lavender aromatherapy.